Innovation in Energy Security and Long-Term Energy Efficiency - Tvaronavičienė, Manuela (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The sustainable development of our planet depends on the use of energy. The growing population of the world inevitably causes an increase in the demand for energy, which, on the one hand, threatens the potential for shortages of energy supply, and, on the other hand, causes the deterioration of the environment.Therefore, our task is to reduce this demand through different innovative solutions (i.e., both technological and social). Social marketing and economic policies can also play a role in affecting the behavior of households and companies, by causing behavioral change oriented to energy stewardship, and an overall switch to renewable energy resources. This book provides a platform for the exchange of a wide range of ideas, which, ultimately, would facilitate the driving of societies to long-term energy efficiency.